Total Power Map to Visibilities (TP2VIS): Joint Deconvolution of ALMA 12 m, 7 m, and Total Power Array Data. (12th April 2019) - Koda, Jin; Teuben, Peter; Sawada, Tsuyoshi; Plunkett, Adele; Fomalont, Ed
Abstract: We present a new package for joint deconvolution of ALMA 12 m, 7 m, and Total Power (TP) data, dubbed "Total Power Map to Visibilities (Tp2vis )". It converts a TP (single-dish) map into visibilities on theCasa platform, which can be input into deconvolvers (e.g., Clean ) along with 12 m and 7 m visibilities. TheTp2vis procedure is based primarily on the one discussed in Koda et al. A manual is presented in theGithub repository (https://github.com/tp2vis/distribute ). Combining data from the different ALMA arrays is a driver for a number of science topics, namely those that probe size scales of extended and compact structures simultaneously (e.g., protostar outflows and environment, AGB stars and planetary nebulae, molecular clouds and cores, and molecular clouds in galaxies). We testTp2vis using model images, one with a single Gaussian and another that mimics the internal structures of giant molecular clouds. The result shows that the better uv coverage withTp2vis visibilities clearly helps the deconvolution process and reproduces the model image within errors of only 5% over two orders of magnitude in flux. In the Appendix, we describe how the model image is generated.